Creative accounting determination and financial reporting quality: The integration of transparency and disclosure - Ibtihal A. Abed; Nazimah Hussin; Hossam Haddad; Tareq Hammad Al-Mubaydeen (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
The phenomenon of creative accounting has attracted the attention of researchers for decades, especially in the financial sector for its implications on the quality of financial reporting. Although several procedures have been developed by researchers and practitioners to determine any manipulation in financial reporting, the practice of creative accounting is still prevalent, resulting in poor quality financial reporting. The present study investigated the moderating role of transparency and disclosure with respect to enhancing the impact of creative accounting determinants and financial reporting quality in the context of commercial banking. A deductive research method driven by a survey questionnaire is used to examine the proposed hypotheses and attain the designed objectives. The analysed data provide a theoretical conceptualisation and practical validation for the integration of the moderator in the relationship between creative accounting determinants and financial reporting quality in banks, with significant advantages. Furthermore, the present research findings show that the degree of impact for creative accounting determinants is linked to the aspects of transparency and disclosure. Lastly, the results present concurrent evidence of the flexibility of creative accounting determinants with implications for transparency and disclosure and financial reporting quality.
Keywords: 650; ethical issues; disclosure quality; internal control; ownership structure; qualitativecharacteristics; manipulation; information asymmetry; commercial banks